Facile synthesis and photocatalytic activity of ZnO/zinc titanate core–shell nanorod arrays. (2nd February 2018) - He, Ding-Chao; Fu, Qiu-Ming; Ma, Zhi-Bin; Zhao, Hong-Yang; Tu, Ya-Fang; Tian, Yu; Zhou, Di; Zheng, Guang; Lu, Hong-Bing
Abstract: ZnO/zinc titanate core–shell nanorod arrays (CSNRs) were successfully prepared via a simple synthesis process by combining hydrothermal synthesis and liquid phase deposition (LPD). The surface morphologies, crystalline characteristics, optical properties and surface electronic states of the ZnO/zinc titanate CSNRs were characterized by scanning electron microscope, transmission electron microscope, x-ray diffractometer, x-ray photoelectron spectroscopy, PL and ultraviolet (UV)–visible absorption spectra. By controlling the reaction time of LPD, the shell thickness could vary with the reaction time. Furthermore, the impacts of the reaction time and post-annealing temperature on the crystalline structure and chemical composition of the CSNRs were also investigated. The studies of photocatalytic activity under UV light irradiation revealed that the ZnO/zinc titanate CSNRs annealed at 700 °C with 30 min deposition exhibited the best photocatalytic activity and good stability for degradation of methylene blue. It had been found that the effective separation of photogenerated electron–hole pairs in the CSNRs led to the enhanced photocatalytic activity. Moreover, the ZnO/zinc titanate CSNRs grown on quartz glass substrate could be easily recycled for reuse with almost unchanged photocatalytic activity.